TGWU recruitment publicity, 1964 (1964)
1964 1960-2000 "TGWU recruitment publicity, 1964" [T0407.jpg], 1964 This recruitment advertisement by the Transport & General Workers Union is taken from a leaflet 'Equal pay for equal work: a new deal for women in engineering' published by the Confederation of Shipbuilding and Engineering Unions.